Carbonate cycle and its control factors in Kuroshio source region during the last 190ka BP - Jingtao, Zhao; Chang, Fengming; Li, Tiegang; Qingyun, Nan; Li, Qing (Yanshi Xuebao = Acta Petrologica Sinica, 2008)
Two deep sea cores (Ph05-5, 16.05 degrees N, 124.34 degrees E, water depth 3382m and WP3:22.15 degrees N, 122.95 degrees E, water depth 2700m) retrieved from the Kuroshio source region of the western Philippine Sea were selected to carry out the CaCO
id: 1934; NO: Source type: scholarlyjournals; Object type: Article; Copyright: GeoRef in Process, Copyright 2011, American Geosciences Institute. After editing and indexing, this record will be added to Georef.; CSAUnique: 577070-23; AccNum: 577070-23; ISSN: 1000-0569; Peer Reviewed: true